2020
DOI: 10.3390/ijerph17186677
|View full text |Cite
|
Sign up to set email alerts
|

Green Open Innovation Activities and Green Co-Innovation Performance in Taiwan’s Manufacturing Sector

Abstract: This study investigates the positive effects of an appropriability regime and perceived similarity to green co-innovation performance when considering green open innovation activities as the mediator. It proposes a novel construct, i.e., green open innovation activities, and employs structural equation modeling to test its hypotheses. 190 valid questionnaires were collected from executives in Taiwanese manufacturing companies. Manufacturing activities are regarded as a major source of pollution. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Thus, green innovation is a collaborative relationship between a hospitality firm, its internal partners (employees) and management, and external partners (customers, suppliers, and government). This allows hospitality firms to integrate inside and outside knowledge with their business partners [40,41]. Green innovation in the hospitality industry focuses on the reduction of energy use, the implementation of solar powered technologies, and the use of more-efficient heating systems and the minimisation of solid waste generation.…”
Section: Green Innovation (Gi)mentioning
confidence: 99%
“…Thus, green innovation is a collaborative relationship between a hospitality firm, its internal partners (employees) and management, and external partners (customers, suppliers, and government). This allows hospitality firms to integrate inside and outside knowledge with their business partners [40,41]. Green innovation in the hospitality industry focuses on the reduction of energy use, the implementation of solar powered technologies, and the use of more-efficient heating systems and the minimisation of solid waste generation.…”
Section: Green Innovation (Gi)mentioning
confidence: 99%
“… Li L. et al (2020) pointed out that employee innovation behavior has a significant impact on task performance. Chang (2020) perform found that employee innovation behavior is significantly positively correlated with the work efficiency and performance of the department. Studies have pointed out that employee innovation behavior can improve work efficiency and corporate performance, while increasing employee competitiveness ( Ibidunni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…The research questions of the extracted contributions (that are reported in Table 2) indicated that in many cases, companies are striving in their endeavors to build productive relationships with different stakeholders (Mtapuri et al, 2022;Peña-Miranda et al, 2022;Shaikh & Randhawa, 2022), to create value to their businesses as well as to society (Döll et al, 2022;Ghodbane, 2019;Roszkowska-Menkes, 2018). Very often, they confirmed that open innovation practitioners are promoting organizational governance (Aakhus & Bzdak, 2015;Sánchez-Teba et al, 2021), fair labor practices (Chang, 2020;Herrera & de las Heras-Rosas, 2020;Kumar & Srivastava, 2020;Schmidt-Keilich & Schrader, 2019), environmentally responsible investments (Aakhus & Bzdak, 2015;Cigir, 2018;Mendes et al, 2021;van Lieshout et al, 2021;Yang & Roh, 2019), and consumer-related issues (Greco et al, 2022;Loučanová et al, 2022;Wu & Zhu, 2021;Yang & Roh, 2019), among other laudable behaviors.…”
Section: Open Innovation Opportunitiesmentioning
confidence: 97%